Using UAS with Sniffer4D payload to document volcanic gas emissions for volcanic surveillance - Godfrey, Ian (2022)
A consistent volcanic monitoring program is crucial to the safety of the population and the efficiency of the nation. Costa Rica´s National Commission for Risk Prevention the CNE helps manage this responsibility. The National Observatory for Volcanoes OVSCORI UNA and the Atmospheric Chemistry Laboratory LAQAT-UNA of Universidad Nacional Costa Rica through a joint cooperation both have a strategic interest in monitoring and tracking volcanic activity. One aspect of monitoring volcanoes is tracking the active emissions being released from the craters, subaerial and subaqueous fumaroles, and diffuse degassing through soil and cracks. For this study the Sniffer4D gas detection payload was deployed on an UAS and flown directly into the active West Crater of the Turrialba volcano in 2022 for readings of active emissions. The Turrialba volcano is located 40 km or 25 miles East of San José the Capital city of Costa Rica where the majority of the population live. Between 2016-2017 an eruption column emerged 4,000 meters or 13,123 feet above the summit crater of the Turrialba volcano and dispersed ash in the capital resulting in airport closures. Thus, monitoring the Turrialba volcano is of great importance to the country. The UAS system deployed carried the Sniffer4D which tested for Temperature, Humidity and 9 additional parameters - Sulfur Dioxide SO2 (µg/ m3), Volatile Organic Compounds VOCs (ppm), Carbon Monoxide CO (mg/m3), Carbon Dioxide CO2 (%), Ozone O3 (µg/ m3), Nitrogen Dioxide NO2 (µg/ m3), O3+NO2 and Particulate Matter - PM 1.0, 2.5 & 10. The main objective was to characterize the volcanic plume of Turrialba for all of these parameters to establish a baseline that can be built upon in the future through additional measurements to determine changes in outgassing regime of the volcano. This was the first time the Turrialba volcano has been tested for these parameters.